2008
DOI: 10.1007/s10796-008-9141-0
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of IT as a factor of production: The case of Net-enabled IT assets

Abstract: A great deal of research in the information systems field has focused on the link between IT and firm-level outputs, like productivity and performance. This paper critically examines the economic assumptions and methodological approaches that underlie much of this work. Three important issues and gaps are identified. First, the functional form of the relationship between IT and firmlevel outputs has been inconsistently specified, or overlooked. Second, multiple input and output variables are often arbitrarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…It shows the intensity of ICT implementation within the company (Nevo et al, 2010). In the same vein, we generated indices showing the intensity of implementation of each of the three groups of ICT.…”
Section: Ict Variablesmentioning
confidence: 99%
See 3 more Smart Citations
“…It shows the intensity of ICT implementation within the company (Nevo et al, 2010). In the same vein, we generated indices showing the intensity of implementation of each of the three groups of ICT.…”
Section: Ict Variablesmentioning
confidence: 99%
“…Many authors have suggested that one of the reasons for inconsistent findings about ICT payoffs might be the existence of lag effects since ICT payoff may require time to materialize. However, most of the studies that take time-lags into account relate to large organizations (Brynjolfsson and Hitt, 2000;Brynjolfsson et al, 2002;Devaraj and Kohli, 2003;Lee and Kim, 2006;Nevo et al, 2010) or specific sectors (Das et al, 2011).Our research contributes to the debate about whether ICT creates value for SMEs performance, providing empirical evidence of the relationships between information technologies, organizational innovation and firm performance from a sample of 267 Spanish manufacturing SMEs. We aim to investigate whether ICT resources, including investment and use of specific types of ICT, along with innovative work practices, correlate positively with several dimensions of firm performance, taking into account both direct and indirect effects and both short (less than one year of ICT implementation) and long-term effects (more than five years).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The characteristics of ICT as a factor of production have not been tested in the era of net-enabled ICT assets. Regarding net-enabled ICT assets, diminishing marginal productivity and input substitutability of ICT have been found (Nevo et al 2008). …”
Section: Contribution Of Ictmentioning
confidence: 99%